2013
DOI: 10.1186/1475-925x-12-75
|View full text |Cite
|
Sign up to set email alerts
|

A sparse-projection computed tomography reconstruction method for in vivo application of in-line phase-contrast imaging

Abstract: BackgroundIn recent years, X-ray phase-contrast imaging techniques have been extensively studied to visualize weakly absorbing objects. One of the most popular methods for phase-contrast imaging is in-line phase-contrast imaging (ILPCI). Combined with computed tomography (CT), phase-contrast CT can produce 3D volumetric images of samples. To date, the most common reconstruction method for phase-contrast X-ray CT imaging has been filtered back projection (FBP). However, because of the impact of respiration, lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Recently, IL-PCI experiments carried out on conventional X-ray sources have demonstrated that comparable image quality could be obtained from the benchtop imaging system (Zysk et al, 2012;Larsson et al, 2016). Moreover, the IL-PCI experiments utilizing live animal subjects have made great headway (Wang et al, 2013;Preissner et al, 2018). These progresses may pave the way for the realization of preclinical or clinical IL-PCI systems.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, IL-PCI experiments carried out on conventional X-ray sources have demonstrated that comparable image quality could be obtained from the benchtop imaging system (Zysk et al, 2012;Larsson et al, 2016). Moreover, the IL-PCI experiments utilizing live animal subjects have made great headway (Wang et al, 2013;Preissner et al, 2018). These progresses may pave the way for the realization of preclinical or clinical IL-PCI systems.…”
Section: Discussionmentioning
confidence: 99%
“…100 μm or larger), a 50 kVp scan protocol with large voxel size (35 μm) and 360 projections would be adequate, resulting in 14-24-fold reduction in radiation dose levels and therefore enabling longitudinal imaging studies. Although not investigated in this study, the use of advanced reconstruction algorithms, such as iterative and statistical reconstructions, is likely to further improve image quality 16 56 57 .…”
Section: Discussionmentioning
confidence: 99%
“…The long X-ray exposure period, used in our studies to achieve adequate SNR, may present challenges in gated-CT acquisitions, and therefore, result in longer acquisition times. The use of supplementary techniques , such as forced respiratory systems associated with locking triggered imaging acquisition, multiple-period averaging and compressed sensing methods may facilitate in overcoming these hurdles 16 57 58 .…”
Section: Discussionmentioning
confidence: 99%
“…There exist studies on the minimization of the total imaging time by reducing the number of scanning views while maintaining the imaging time unchanged at each view in PCCT. [1][2][3] In this study, we investigate a different approach to reducing the imaging time in PCCT by lowering its scanning angular range to a limited angular range (LAR) that is less than the full angular range of π. A PCCT scan over a LAR can readily be implemented in PCCT without invoking any hardware changes simply by stopping X-ray illumination and data collection beyond the LAR prescribed.…”
Section: Introductionmentioning
confidence: 99%